2012
DOI: 10.1093/icesjms/fss112
|View full text |Cite
|
Sign up to set email alerts
|

Otolith microstructure analysis to resolve seasonal patterns of hatching and settlement in western Baltic cod

Abstract: Rehberg-Haas, S., Hammer, C., Hillgruber, N., Hüssy, K., and Temming, A. 2012. Otolith microstructure analysis to resolve seasonal patterns of hatching and settlement in western Baltic cod. – ICES Journal of Marine Science, 69: . Previous studies showed that Baltic cod (Gadus morhua) settle to demersal life at a given size, while the annulus is formed seasonally, irrespective of size. The goal of this study was to examine the timing of check formation in juvenile Baltic cod otoliths to validate macrostructural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
15
2
Order By: Relevance
“…Since round goby have a prolonged spawning season, April through to September (Kornis et al, 2012), the distance of the first winter ring to the core may vary considerably between individuals depending on when they had hatched. This may result in difficulties in discriminating between the juvenile settlement ring and first true winter ring (Rehberg-Haas, Hammer, Hillgruber, Hüssy, & Temming, 2012). Also the preparation technique in itself may contribute to this problem, in that the first winter ring may get progressively obscured as the fish gets older and the otolith bigger (Ross & Hüssy, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Since round goby have a prolonged spawning season, April through to September (Kornis et al, 2012), the distance of the first winter ring to the core may vary considerably between individuals depending on when they had hatched. This may result in difficulties in discriminating between the juvenile settlement ring and first true winter ring (Rehberg-Haas, Hammer, Hillgruber, Hüssy, & Temming, 2012). Also the preparation technique in itself may contribute to this problem, in that the first winter ring may get progressively obscured as the fish gets older and the otolith bigger (Ross & Hüssy, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Teleost otoliths have provided a powerful lens through which to better understand fish biology and ecology (Popper et al, ). By studying the structure and chemical composition of otoliths, researchers have extracted a wealth of valuable information about fish age (Campana & Thorrold, ), metabolism and somatic growth rates (Armstrong et al, ; Colloca et al, ; Hoff & Fuiman, ), the timing of major life‐history events (Neilson et al, ; Rehberg‐Haas et al, ) and even the chemical composition of the environment (Elsdon & Gillanders, , ). In particular, the saccular (sagittal) otolith, one of three paired otoliths found within the inner ear, displays high interspecific variation in shape and size and relatively less intraspecific variation, making it useful for discriminating between fish species (Campana, ; Schellart & Popper, ; Tuset et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Macrostructural settlement-marks, a type of discontinuity (or check) in a regulate seasonal zone, have for example been described in several species, including red gurnard (Aspitrigla cuculus) (Colloca et al, 2003), Baltic cod (Gadus morhua) (Rehberg-Haas et al, 2012) and various species of tropical reef fish (Wilson and McCormick, 1997). Settling marks have also been suggested as a possible source for misinterpretation of age because they may appear as false annuli (Gauldie, 1987;Waldron and Kerstan, 2001;Rehberg-Haas et al, 2012). External factors such as reduced food availability and different prey type (Hüssy et al, 2003) or declined temperature (Toole et al, 1993) have all been suggested as probable causes to settling marks.…”
Section: Impacts Of Life History Events In the Otolith Growth Structurementioning
confidence: 99%
“…Rollefsen, 1933;Campana and Casselman, 1993), and using micro-or macrostructural analyses to back-calculate individual size and growth rate (Otterlei et al, 2002;Hüssy et al, 2003) and indicate timing or age at life history events (e.g. Rollefsen, 1933;Rehberg-Haas et al, 2012). Rollefsen (1933;1934b;1934a;1935) and Dannevig (1933) showed that otoliths as a mean to determine age was more favourable than scales.…”
Section: Stock Monitoring and Otolith Collectionmentioning
confidence: 99%